Effect of processing parameter on chemical composition of cucurbita moschata extract / Nurul Najihah Satar, Aina Irdiana Mohd Yusmadi and Abdullah Ammar Abdul Halim - Satar, Nurul Najihah; Mohd Yusmadi, Aina Irdiana; Abdul Halim, Abdullah Ammar (2021)
Pumpkin (Cucurbita Moschata) is a vital tropical vegetable that grows fully-fledged in everyplace around the world. This tropical pumpkin (C.moschata) goes to the Cucurbitaceous family. C.moschata is frequently used in traditional medications since the seed has a high source of energy such as protein, potassium, phosphorus, iron and b-carotene and possesses a wide range of therapeutic activities such as anthelmintic, antioxidant and antibacterial. The extraction that involves different processing parameters are crucial to obtain bioactive compounds from C.moschata. Therefore, this current research study the effect of different parameters towards the extraction yield of bioactive compounds. Parameters that are involved are between types of solvent, temperature and method of detection; drying method, time and detection method; temperature and method of detection. These parameters were assessed by using the Taguchi method. The highest delta in S/N ratio indicates the most influence factor towards the extraction yield of bioactive compounds. The result obtained showed that temperature is the most influential factor as compared to the types of solvent and method of detection. While the time is more influenced compared with the detection method. Other than that, temperature has the most influence when compared with the detection method. Temperature and time were statistically significant which have a value of P<0.05 as compared to the other parameters. Hence, it can be concluded that time and temperature have significant effects toward the extraction yield of bioactive compounds in Cucurbita Moschata.